2019
DOI: 10.1557/jmr.2019.146
|View full text |Cite
|
Sign up to set email alerts
|

DFT based study on structural stability and transport properties of Sr3AsN: A potential thermoelectric material

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Yan et al predicted κ L values of 45 compounds, and the error compared with experimental values remained within 1 order of magnitude. More importantly, the results show that κ L value is more possible to be overestimated using the empirical equation in the range of low κ L values. , Figure demonstrates the κ L values calculated by the empirical equation as a function of the accurate κ L reported in the literature at 300 K, which also proves this finding. In this work, structural information and general properties of all materials come from Materials Project Database, , including M̅ , V , n , d , and B .…”
Section: Methodssupporting
confidence: 73%
See 3 more Smart Citations
“…Yan et al predicted κ L values of 45 compounds, and the error compared with experimental values remained within 1 order of magnitude. More importantly, the results show that κ L value is more possible to be overestimated using the empirical equation in the range of low κ L values. , Figure demonstrates the κ L values calculated by the empirical equation as a function of the accurate κ L reported in the literature at 300 K, which also proves this finding. In this work, structural information and general properties of all materials come from Materials Project Database, , including M̅ , V , n , d , and B .…”
Section: Methodssupporting
confidence: 73%
“…Many efforts demonstrate that some perovskites are potential low thermal conductivity materials. Lee et al found CsSnI 3 had ultralow κ L value due to cluster rattling mechanism. Low κ L value of Sr 3 AsN was also confirmed . Structural prototypes Rb 2 SnBr 6 and Rb 2 NaScI 6 fall into categories of halide double perovskites, which attracts more attention recently. To the best of our knowledge, the low κ L values of structural prototypes CsCu 3 O 2 , Rb 2 SnAs 2 , RbPS 3 , CsVI 3 , and Rb 2 As 3 have not been reported in the literature so far.…”
Section: Results and Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…For example, Sr 3 SnO has two kinds of anion atoms, O 2− and Sn 4− , the latter of which is an unusual negative oxidation state of group-14 elements. The unique crystal and electronic structures of antiperovskites have been investigated also as possible candidates for thermoelectric materials in experimental 46 and theoretical [47][48][49][50][51][52][53][54][55][56][57][58][59] studies. Experimental realization of the carrier control and a high Seebeck coefficient of around 100 µVK −1 together with a metallic resistivity and a relatively low thermal conductivity of around 2 Wm −1 K −1 at room temperature is promising 46 .…”
Section: Introductionmentioning
confidence: 99%